Aprendiendo de mi cuerpo. - Reinoso Gutiérrez, Diana Carolina (2017)
The present research aims to design a web page for adolescents 12 to 14 years old of the Independiente del Valle Football Club to help prevent the incidence of early pregnancies. In the first place, important concepts related to sexuality and youth that are to be approached in the Web page taking into account the codes of interaction most appropriate to the perspective of authors such as Foucault, Dolto, and others are established at the theoretical level age at which the development of the product was directed. This study made it possible to investigate the needs of these adolescents on sex education in order to determine the main multimedia resources to be used in the web page from the fusion of the theoretical perspectives of the educational and communicational tasks in relation to the learning and the knowledge of the own body. In addition, the study was based on the theories of Tajfel's social identity and critical communication theory and from the applied surveys it was possible to know the main knowledge that these adolescents have of sexuality and the processes related to this subject, is so it allowed to identify a diagnosis to delimit the contents of the web page and the mechanisms to guide the management of the learning. The website was an educational learning platform according to the management of knowledge associated with the information needs of this target group.